Fulfilling the Requirements and Realization Between Jurisprudence, Arithmetic Sciences and Engineering (Islamic Sciences Journal, 2023)
The legal rulings came in the Qur’an and the Sunnah to be valid for every time and place, and it is known that the legal texts are limited, and the facts from the beginning of the revelation to the advent of the Hour are unlimited. Sharia law and the extent of its realization in the person and the event, and the issues of arithmetic and geometry are among the ways to achieve the basis of the ruling, and knowledge of the account which are necessary in some issues to achieve the right to fatwa and judiciary.
Keywords: Achieving the assignment. Download provisions. The jurisprudence of nawazil. Reality jurisprudence. Graduation of jurisprudence rulings. Judiciary and fatwa